Deux programmes d’éducation environnementale pour la conservation des grands singes africains: Club Ebobo et Club P.A.N. - Claudia Borchers; Julia Riedel; Christophe Boesch; Thomas Breuer (Revue de Primatologie)
In this article we will present two long term environmental education projects which aim to raise awareness about the protection of great apes and their tropical rainforest habitat. Club Ebobo is based around the Nouabalé-Ndoki National Park, Republic of Congo and Club P.A.N. around the Taï National Park, Ivory Coast. In both projects, children learn about the importance of the conservation of their regional ecosystems and the protection of the endangered great apes living close to them – the west African chimpanzee (Pan troglodytes verus) in Ivory Coast, and the western lowland gorilla (Gorilla gorilla gorilla) and common chimpanzee (Pan troglodytes troglodytes) in the Republic of Congo. Both projects take place in villages close to the named national parks and are conducted with the help of regional coordinators and teachers. The projects are well accepted in the region and are a part of the conservation efforts conducted for the conservation of great apes. We summarize the success and challenges that we encountered with both nature clubs and make some recommendations on how to improve environmental education.